Modifying a 3D-Printed Ti6Al4V Implant with Polydopamine Coating to Improve BMSCs Growth, Osteogenic Differentiation, and In Situ Osseointegration In Vivo - Wang, Hui; Yuan, Changyong; Lin, Kaili; Zhu, Rui; Zhang, Shilei (Frontiers in Bioengineering and Biotechnology, 2021)
Nowadays, 3D printing technology has been applied in dentistry to fabricate customized implants. However, the biological performance is unsatisfactory. Polydopamine (PDA) has been used to immobilize bioactive agents on implant surfaces to endow them with multiple properties, such as anti-infection and pro-osteogenesis, benefiting rapid osseointegration. Herein, we fabricated the PDA coating on the 3D-printed implant surface (3D-PDA) via the in-situ polymerization method. Then the 3D-PDA implants’ pro-osteogenesis capacity and the osseointegration performance were evaluated in comparison to the 3D group. The in vitro results revealed that the PDA coating modification increased the hydrophilicity of the implants, deriving the improvement of the adhesion, propagation, and osteogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) in vitro. Additionally, the 3D-PDA implant improved osteointegration performance in vivo. The present study suggested that PDA coating might be a feasible strategy to optimize 3D-printed implant surface, making a preliminary research basis for the subsequent work to immobilize bioactive factors on the 3D-printed implant surface.